Virus study for continuous low pH viral inactivation inside a coiled flow inverter. Issue 4 (31st December 2018) - David, Laura; Maiser, Benjamin; Lobedann, Martin; Schwan, Peter; Lasse, Michael; Ruppach, Horst; Schembecker, Gerhard
Abstract: Continuous processing for the production of monoclonal antibodies (mAb) gains more and more importance. Several solutions exist for all the necessary production steps, leading to the possibility to build fully continuous processes. Low pH viral inactivation is a part of the standard platform process for mAb production. Consequently, Klutz et al. introduced the coiled flow inverter (CFI) as a tool for continuous low pH viral inactivation. Besides theoretical calculations of viral reduction, no viral clearance study has been presented so far. In addition, the validation of continuous viral clearance is often neglected in the already existing studies for continuous processing. This study shows in detail the development and execution of a virus study for continuous low pH viral inactivation inside a CFI. The concept presented is also valid for adaptation to other continuous viral clearance steps. The development of this concept includes the technical rationale for an experimental setup, a valid spiking procedure, and finally a sampling method. The experimental results shown represent a viral study using xenotropic murine leukemia virus as a model virus. Two different protein A (ProtA) chromatography setups with varying pH levels were tested. In addition, one of these setups was tested against a batch experiment utilizing the same process material. The results show that sufficient low pH viral inactivation (decadic logarithm reduction value >4) was achieved in all experiments. Complete viral inactivation took place within the first 14.5 min for both continuous studies and the batch study, hence showing similar results. This study therefore represents a successful virus study concept and experiment for a continuous viral inactivation step. Moreover, it was shown that the transfer from batch results to the continuous process is possible. This is accomplished by the narrow residence time distribution of the CFI, showing how close the setup approaches the ideal plug flow and with that batch operation. Abstract : Continuous processing for the production of monoclonal antibodies (mAb) gains more and more importance. This study represents a first concept for virus studies for continuous processes and its experimental execution.